ADMINISTRATIVE SYSTEM DESIGN APPLICATIONS HOSPITAL PATIENTS IN HOSPITALS SARI ASIH USING THE LANGUAGE PROGRAMMING MICROSOFT VISUAL BASIC 6.0 - Angga Surya Pratama; Elly Agustina J.,S.Kom.,MMSI (Jurnal Sistem Informasi, 2009)
In essence the hospital during this asih Mampang Depok administration in patientsreceiving inpatient care is still done manually so often cause errors in the delay ofpatient care information.Based on these problems, I am interested to try to help resolve the problem bycreating a computerized system and the author will use the display programanmicrosoft Visual Basic 6.0.